Teaching specificity in word choice - Tumangday, Miriam Sarno 1930- ([Quezon City s.n.], 1965)
This study presents organized instructional materials in teaching students the pleasant way of proper word selection. A sample lesson plan on teaching specificity in word-choice, illustrating the application of the see-hear-and-do method integrated with structure and speech improvement can also be found in this study.
Thesis (M.A.T.)--University of the Philippines
Keywords: Vocabulary